THE ROLE OF COMPANIONS AND SUCCESSORS’ REPORTS IN AL-ṬABARI’S TAFSIR: A SOURCE-CRITICAL ANALYSIS (The Journal of Interdisciplinary Human Studies, 2025)
This study investigates the methodological significance of Companions(ṣaḥаba) and Successors (tаbiʿun) reports in al-Ṭabari’s Jаmiʿ al-bayаn ʿan taʾwilаy al-Qurʾаn, one of the earliest comprehensive exegetical works in the Islamic tradition.Through source-critical analysis, the research explores how al-Ṭabari structures,evaluates, and privileges transmitted reports (athаr) in his hermeneutical framework.The findings demonstrate that the authority of the Companion and Successor traditionfunctions as the backbone of ṭabarian exegesis, informing linguistic explanation, legalreasoning, and theological positioning. Al-Ṭabari’s rigorous isnаd-based methodologyshows multilayered reliance on early Islamic transmitters, yet employs rationalpreference (tarjiḥ) when divergent interpretations arise. This study contributes tounderstanding classical tafsir formation and the epistemological hierarchy governingearly Qurʾаnic interpretation.
Keywords: al-Ṭabari, Jаmiʿ al-bayаn; tafsir; Companions, Successors; isnаd criticism; Qurʾаnic exegesis; manba studies